2020
DOI: 10.1136/gutjnl-2019-320135
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin maintains gut microbe homeostasis by balancing α-Proteobacteria and Lachnospiraceae

Abstract: ObjectiveAntimicrobial peptides (AMPs) play essential roles in maintaining gut health and are associated with IBD. This study is to elucidate the effect of angiogenin (ANG), an intestine-secreted AMP, on gut microbiota and its relevance with IBD.DesignThe effect of ANG on microbiota and its contribution to colitis were evaluated in different colitis models with co-housing and faecal microbiota transplantation. ANG-regulated bacteria were determined by 16S rDNA sequencing and their functions in colitis were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 44 publications
5
84
0
Order By: Relevance
“…Oral administration of Ang-1 is known to restore the intestinal microbiota composition of Ang-1-deficient mice, ultimately relieving colitis. Therefore, targeting Ang could be a potential therapeutic target for intestinal diseases associated with dysbacteriosis ( 117 ).…”
Section: Microbiome Influences Immunotherapy and Antiangiogenesis Therapymentioning
confidence: 99%
“…Oral administration of Ang-1 is known to restore the intestinal microbiota composition of Ang-1-deficient mice, ultimately relieving colitis. Therefore, targeting Ang could be a potential therapeutic target for intestinal diseases associated with dysbacteriosis ( 117 ).…”
Section: Microbiome Influences Immunotherapy and Antiangiogenesis Therapymentioning
confidence: 99%
“…In these studies, a higher abundance of Capnocytophaga in the oral cavity was associated with oral diseases, and it may be a promising biomarker for predicting esophageal squamous cell carcinoma. In a previous study, Lachnospiraceae functioned as a short-chain fatty acid producer [ 35 ], and this family of anaerobic bacteria is reportedly found at relatively low levels in colorectal cancer patients [ 16 , 36 ]. This result is consistent with the present study, in which there was a higher abundance of Lachnospiraceae in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“… Leccese et al (2020) found that Lactobacillus acidophilus LA1 or Lactobacillus paracasei 101/37 (belonging to the Lactobacillaceae family, Firmicutes phylum) can effectively reduce adherent-invasive E. coli adhesion to HT29 (human colorectal adenocarcinoma cell), as well as reducing biofilm formation. Sun et al (2021) found that Anaerostipes sp. and Blautia sp.…”
Section: Discussionmentioning
confidence: 99%